2017
DOI: 10.1186/s12711-017-0314-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection of QTL for traits related to adaptation to sub-optimal climatic conditions in chickens

Abstract: BackgroundGrowth traits can be used as indicators of adaptation to sub-optimal conditions. The current study aimed at identifying quantitative trait loci (QTL) that control performance under variable temperature conditions in chickens.MethodsAn F2 population was produced by crossing the Taiwan Country chicken L2 line (selected for body weight, comb area, and egg production) with an experimental line of Rhode Island Red layer R- (selected for low residual feed consumption). A total of 844 animals were genotyped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Additionally, different QTL can be detected depending on the method and the density of markers used. In this context, in a study performed to identify QTL that control performance under variable temperature conditions in chickens, Lien et al [44] compared QTL detected in an F2 chicken population by GWAS using univariate linear mixed model (GEMMA software) and using interval mapping method (QTLMap software). This study showed that eight QTL were detected by QTLMap, 47 were detected by GEMMA and from those, only two were common to both approaches [44].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, different QTL can be detected depending on the method and the density of markers used. In this context, in a study performed to identify QTL that control performance under variable temperature conditions in chickens, Lien et al [44] compared QTL detected in an F2 chicken population by GWAS using univariate linear mixed model (GEMMA software) and using interval mapping method (QTLMap software). This study showed that eight QTL were detected by QTLMap, 47 were detected by GEMMA and from those, only two were common to both approaches [44].…”
Section: Discussionmentioning
confidence: 99%
“…A 24.08 Kb QTL on GGA24 (GGA24: 5.73–5.75 Mb) was identified for the six weight traits. According to the Animal QTL Database 8 , this region has been recorded as a QTL (GGA24: 4.3–6.0 Mb) for BW08 in an F2 population (Taiwan local chicken line L2 × experimental Rhode Island Red line; Lien et al, 2017 ). This region contains only one candidate gene ( DRD2 ), which encodes the D2 subtype of the dopamine receptor.…”
Section: Discussionmentioning
confidence: 99%
“…To date, relatively few GWAS have been performed on comb traits, among which only two studies are established on the quantitative characters of combs. One was conducted on CL, CH, and CW using 600 K SNP arrays ( Shen et al, 2016 ) and the other on CA using a 60 K SNP chip ( Lien et al, 2017 ). Compared with these two studies, the magnitude of SNPs used in our study was much larger.…”
Section: Discussionmentioning
confidence: 99%